1999
DOI: 10.30843/nzpp.1999.52.11578
|View full text |Cite
|
Sign up to set email alerts
|

Pasture tolerance to the herbicide metsulfuron-methyl

Abstract: Trials were carried out in spring and autumn at two locations in New Zealand to measure the effects of metsulfuron-methyl on pasture production and composition. Metsulfuron-methyl at 3-12 g/ha resulted in 20-45% loss of herbage production. This was particularly evident for two months after spraying, with no significant reduction in dry matter yield 3 months after treatment in spring. The effect on pasture composition was more persistent. Metsulfuron-methyl, along with clopyralid and picloram + 2,4-D completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Less than 5% visual injury was observed across all summer-applied herbicide treatments (Table 3.1). These results are similar to other authors who have reported little to no signs of visual tall fescue injury following applications of these herbicides (James et al, 1999;. This decrease in tall fescue injury for all summer-applied treatments is likely associated with the stage of tall fescue at the time of the summer compared to spring herbicide applications.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Less than 5% visual injury was observed across all summer-applied herbicide treatments (Table 3.1). These results are similar to other authors who have reported little to no signs of visual tall fescue injury following applications of these herbicides (James et al, 1999;. This decrease in tall fescue injury for all summer-applied treatments is likely associated with the stage of tall fescue at the time of the summer compared to spring herbicide applications.…”
Section: Resultssupporting
confidence: 90%
“…Spring-applied metsulfuron provided the highest visual injury to tall fescue resulting in 22% injury one month after treatment (MAT) ( Table 3.1). Other authors have also observed significant injury to tall fescue injury following applications of metsulfuron (Bradley and Kendig, 2004;James et al 1999;. The addition of 2,4-D and dicamba to metsulfuron decreased tall fescue injury in June by 9% (Table 3.1).…”
Section: Resultsmentioning
confidence: 84%
“…Metsulfuron-methyl is another ALS-inhibitor herbicide used in pastures, because of its excellent translocation properties, but its lack of selectivity means that it is used as a spot application [39] or with wiper applications [41]. Boom spraying of this herbicide is not recommended as this will lead to the complete removal of clovers and suppression of ryegrass and will also affect the re-establishment of pasture species due to residues lasting up to three months within the soil depending on soil pH [57,58].…”
Section: Acetolactate Synthase-inhibitor (Als-inhibitor) Herbicidesmentioning
confidence: 99%
“…No noticeable differences were present in tall fescue injury between any of the herbicide-treated or non-treated plots (data not shown) by the time of the spring harvest following treatment. Spring applications of metsulfuron- containing herbicides are known to cause some visual injury and stunting to tall fescue forages (1,9). However, other research has shown that late-season applications of these same treatments will result in little to no injury in tall fescue (19).…”
Section: Tall Fescue Injurymentioning
confidence: 99%